Adhesive as well as raw material composition, preparation method and application thereof

By using cationic emulsifier and sodium bicarbonate to form uniform pores during latex drying, the problems of uneven pore distribution and poor sound absorption effect of traditional sound insulation boards are solved, and more efficient sound insulation effect and plate density are achieved. Improved strength, suitable for a variety of sheet materials.

CN119286434APending Publication Date: 2025-01-10SHANGHAI CHANGFA NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411557580.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The pore distribution of traditional sound insulation boards is uneven and the sound absorption effect is poor. The selection of emulsifiers and process parameters are complex, which increases production costs and time, and has limited applicability to different materials.

Method used

Using an adhesive raw material composition, including seed emulsion, styrene, butadiene, carboxylic acid monomer, molecular weight regulator, initiator and alkaline substance, uniform pores are formed under high temperature and high pressure through cationic emulsifier and sodium bicarbonate. , combined with the design of core layer and shell polymer, achieve uniform distribution of pores and increase of the density and strength of the plate.

Benefits of technology

It achieves better uniform air pore distribution and board density and strength stability, improves sound insulation effect, and reduces production costs, and is suitable for a variety of board materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005116943940000071
    Figure BDA0005116943940000071
  • Figure BDA0005116943940000081
    Figure BDA0005116943940000081
  • Figure BDA0005116943940000091
    Figure BDA0005116943940000091
Patent Text Reader

Abstract

The invention discloses an adhesive as well as a raw material composition, a preparation method and application thereof. The adhesive comprises the following raw materials in parts by weight: 3-6 parts of a seed emulsion, 60 parts of styrene, 30-40 parts of butadiene, 1-3 parts of a carboxylic acid monomer, 0.5-1.5 parts of a molecular weight regulator, 0.8-2 parts of an initiator and 0.5-2 parts of an alkaline substance, wherein the seed emulsion comprises a cationic emulsifier and sodium bicarbonate. The emulsion polymerization technology is adopted, air holes are formed through the cationic emulsifier, meanwhile, the core layer is the water-soluble polymer, the shell layer is the high polymer which is formed through monomer polymerization and has a bonding effect, and therefore the air holes of the formed board can be evenly distributed, the sound insulation effect of the board is improved, the density and strength of the board are improved, and the production cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adhesives, and in particular relates to an adhesive, a raw material composition thereof, a preparation method thereof and an application thereof. Background Art

[0002] Sound insulation board is a material used to reduce noise transmission and is widely used in the fields of construction, automobiles, etc. Traditional sound insulation board usually adopts a porous structure to absorb noise energy to achieve the effect of sound insulation. However, there are some problems with traditional porous sound insulation board, such as uneven pore distribution and poor sound absorption effect.

[0003] In order to improve the above-mentioned problems of traditional sound insulation panels, special emulsifiers are usually used at present to form pores in the foam produced by drying latex under high temperature and high pressure, thereby achieving uniform distribution of pores in the panel. By controlling the composition and process parameters of the emulsifier, the size and distribution of the pores can be adjusted to improve the sound insulation effect of the panel. Although the prior art has achieved certain results in improving the sound insulation effect of the panel, there are still some problems. First, the selection and use of emulsifiers require certain skills and experience, and the production process is relatively complicated; secondly, since the composition and process parameters of the emulsifier have a certain influence on the formation of pores, continuous testing and adjustment are required, which increases production costs and time costs. In addition, the applicability of the prior art to different materials is limited and cannot meet the needs of various panels. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides an adhesive, a raw material composition thereof, a preparation method thereof and an application thereof.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] In one aspect, the present invention provides a raw material composition of an adhesive, which comprises the following raw materials in parts by weight:

[0007] 3-6 parts of seed emulsion, 60 parts of styrene, 30-40 parts of butadiene, 1-3 parts of carboxylic acid monomer, 0.5-1.5 parts of molecular weight regulator, 0.8-2 parts of initiator, 0.5-2 parts of alkaline substance;

[0008] Wherein, the seed emulsion includes a cationic emulsifier and sodium bicarbonate.

[0009] In some embodiments, the carboxylic acid monomer is selected from acrylic acid and / or methacrylic acid;

[0010] In some embodiments, the molecular weight regulator is selected from one of n-dodecyl mercaptan, tert-dodecyl mercaptan, and n-butyl mercaptan;

[0011] In some embodiments, the initiator is selected from one of ammonium persulfate / sodium bisulfite, potassium persulfate / sodium bisulfite, hydrogen peroxide / tartaric acid, hydrogen peroxide / diaobaikuai, ammonium persulfate / ferrous sulfate, hydrogen peroxide / ferrous sulfate, wherein the ratio of oxidant:reducing agent is 1:0.2-0.8;

[0012] In some embodiments, the alkaline substance is selected from alkali metal hydroxides, preferably, the alkaline substance is sodium hydroxide or potassium hydroxide;

[0013] In some embodiments, the raw material composition of the adhesive further includes deionized water; preferably, the weight proportion of the deionized water is 100 to 120 parts.

[0014] In some embodiments, the seed emulsion includes the following raw materials in parts by weight:

[0015] 183-210 parts of deionized water, 3-8 parts of cationic emulsifier, 1-2 parts of initiator, 5-10 parts of carboxymethyl cellulose, 35 parts of lignin, and 1-3 parts of sodium bicarbonate.

[0016] In some embodiments, the cationic emulsifier is selected from at least one of methyl alkyl ammonium chlorides, wherein the alkyl group is preferably a C8-C18 alkyl group, more preferably a C8-C16 alkyl group, and most preferably a C12-C16 alkyl group. As a further preferred embodiment, the present invention selects a dodecyl series of emulsifiers.

[0017] In some embodiments, the molecular weight of the lignin is 500-1000.

[0018] In another aspect, the present invention provides a method for preparing an adhesive, wherein the raw materials of the adhesive include the above-mentioned raw material composition of the adhesive, and specifically comprises the following steps:

[0019] (1) After the polymerization kettle is evacuated, deionized water and seed emulsion are added, stirred, heated to 50-60°C, and initiator is added;

[0020] (2) adding a mixed solution of styrene, butadiene, carboxylic acid monomer and molecular weight regulator dropwise for free radical emulsion polymerization for 4 to 6 hours, and then carrying out heat preservation reaction;

[0021] (3) After cooling, the pH value is adjusted with an alkaline substance, and the mixture is filtered to obtain the ALC sheet adhesive.

[0022] In step (1), the vacuum degree of the polymerization kettle is -0.08 MPa;

[0023] In step (2), the temperature of the free radical emulsion polymerization is 50-60° C.;

[0024] In step (2), the temperature of the insulation reaction is 50 to 70° C.;

[0025] In step (2), the insulation reaction time is 1 to 3 hours.

[0026] In step (3), the pH value is adjusted to 6-7.

[0027] In step (1), the method for preparing the seed emulsion comprises the following steps:

[0028] S1. After the polymerization kettle is evacuated, deionized water and cationic emulsifier are added, stirred, and the temperature is raised to 60-70°C;

[0029] S2, adding an initiator, carboxymethyl cellulose, lignin and sodium bicarbonate to react, and keeping the temperature after the reaction is completed to obtain the seed emulsion.

[0030] In step S1, the vacuum degree of the polymerization kettle is -0.08MPa;

[0031] In step S2, the reaction time is 1 to 3 hours;

[0032] In step S2, the insulation reaction time is 1 to 2 hours;

[0033] In step S2, the temperature of the heat preservation reaction is 60-70°C.

[0034] The third aspect of the present invention provides an adhesive, which is prepared by the adhesive preparation method as described above.

[0035] A fourth aspect of the present invention provides use of the adhesive in ALC boards.

[0036] The beneficial effects of the present invention are:

[0037] 1. On the one hand, the present invention uses a special cationic emulsifier to make the core layer a water-soluble polymer and the shell layer a high polymer with bonding effect formed by the polymerization of monomers. In the later ALC board coating preparation process, the cationic emulsifier can release a part of ammonia due to the strong alkalinity of the coating. The generated ammonia can make the coating loose and porous and expand in volume; on the other hand, the sodium bicarbonate wrapped in the core layer forms pores in the foam generated during the latex drying process under high temperature and high pressure. These pores can be evenly distributed in the formed board. Compared with the prior art, the present invention can better achieve a uniform distribution of pores, thereby further improving the sound insulation effect of the board.

[0038] 2. The present invention can increase the density and strength of the board by forming pores during the drying process. Compared with the prior art, the present technical solution can more effectively control the formation and distribution of pores, thereby making the density and strength of the board more stable and uniform.

[0039] 3. Compared with the prior art, the present invention can utilize cationic emulsifiers more efficiently and reduce production costs while ensuring uniform distribution of pores. DETAILED DESCRIPTION

[0040] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications. In addition, the reagents and raw materials used in the present invention are commercially available. Among them, the molecular weight of lignin is 500 to 1000.

[0041] Example 1

[0042] An adhesive, the raw material composition of which includes the following components in parts by weight, see Table 1;

[0043] Table 1

[0044] Specific compounds Quality (parts) Deionized water 100 Seed lotion 3 Styrene 60 Butadiene 30 Carboxylic acid monomer: acrylic acid 1 Molecular weight regulator: tert-dodecyl mercaptan 0.5 Initiator: ammonium persulfate 0.6 Initiator: Sodium bisulfite 0.3 Alkaline substances: sodium hydroxide 0.5

[0045] The seed emulsion includes the following components in parts by weight, see Table 2:

[0046] Table 2

[0047] Specific compounds Quality (parts) Deionized water 200 Cationic emulsifier: Methyl dodecyl ammonium chloride 3 Initiator: ammonium persulfate 0.67 Initiator: Sodium bisulfite 0.33 Carboxymethyl cellulose 10 Lignin 35 Sodium bicarbonate 1

[0048] A. A method for preparing a seed emulsion comprises the following steps:

[0049] S1. After the polymerization kettle is evacuated to -0.08MPa, deionized water and cationic emulsifier are added, stirred and heated to 60°C;

[0050] S2, add initiator, carboxymethyl cellulose, lignin, sodium bicarbonate, react for 2 hours, heat to 70°C and keep warm for 1 hour to obtain the product.

[0051] B. A method for preparing an adhesive, comprising the following steps:

[0052] (1) After the polymerization kettle is evacuated to -0.08 MPa, deionized water and seed emulsion are added, stirred and heated to 50°C; initiator is added;

[0053] (2) adding dropwise a mixture solution of styrene, butadiene, carboxylic acid monomer, and molecular weight regulator to carry out free radical emulsion polymerization at a polymerization temperature of 56° C. for a dropwise addition time of 4 h, and heating to 56° C. for 2 h;

[0054] (3) After cooling, the pH value is adjusted to 6-7 with an alkaline substance, and after filtering, an adhesive is obtained.

[0055] Example 2

[0056] An adhesive, the raw material composition of which includes the following components in parts by weight, see Table 3;

[0057] Table 3

[0058] Specific compounds Quality (parts) Deionized water 119 Seed lotion 3 Styrene 60 Butadiene 40 Carboxylic acid monomer: methacrylic acid 2 Molecular weight regulator: n-dodecyl mercaptan 1.5 Initiator: Potassium persulfate 1 Initiator: Sodium bisulfite 0.5 Alkaline substances: potassium hydroxide 2

[0059] The seed emulsion includes the following components in parts by weight, see Table 4;

[0060] Table 4

[0061] Specific compounds Quality (parts) Deionized water 210 Cationic emulsifier: Methyl dodecyl ammonium chloride 8 Initiator: Potassium persulfate 1.33 Initiator: Sodium bisulfite 0.67 Carboxymethyl cellulose 8 Lignin 35 Sodium bicarbonate 3

[0062] A. A method for preparing a seed emulsion comprises the following steps:

[0063] S1. After the polymerization kettle is evacuated to -0.08MPa, deionized water and cationic emulsifier are added, stirred and heated to 70°C;

[0064] S2, add initiator, carboxymethyl cellulose, lignin, sodium bicarbonate, react for 2 hours, heat to 70°C and keep warm for 1 hour to obtain the product.

[0065] B. A method for preparing an adhesive, comprising the following steps:

[0066] (1) After the polymerization kettle is evacuated to -0.08 MPa, deionized water and seed emulsion are added, stirred and heated to 60°C; initiator is added;

[0067] (2) adding dropwise a mixture solution of styrene, butadiene, carboxylic acid monomer, and molecular weight regulator to carry out free radical emulsion polymerization at a polymerization temperature of 60° C. for a dropwise addition time of 6 h, and heating to 60° C. for 2 h;

[0068] (3) After cooling, the pH value is adjusted to 6-7 with an alkaline substance, and after filtering, an adhesive is obtained.

[0069] Example 3

[0070] An adhesive, the raw material composition of which includes the following components in parts by weight, see Table 5;

[0071] Table 5

[0072]

[0073]

[0074] The seed emulsion includes the following components in parts by weight, see Table 6:

[0075] Table 6

[0076] Specific compounds Quality (parts) Deionized water 198 Cationic emulsifier: Methyl dodecyl ammonium chloride 8 Initiator: Hydrogen peroxide 1 Initiator: Ferrous sulfate 0.5 Carboxymethyl cellulose 5 Lignin 35 Sodium bicarbonate 3

[0077] A. A method for preparing a seed emulsion comprises the following steps:

[0078] S1. After the polymerization kettle is evacuated to -0.08MPa, deionized water and cationic emulsifier are added, stirred and heated to 60°C;

[0079] S2, add initiator, carboxymethyl cellulose, lignin and sodium bicarbonate, react for 3 hours, raise the temperature to 60°C and keep it for 2 hours to obtain the product.

[0080] B. A method for preparing an adhesive, comprising the following steps:

[0081] (1) After the polymerization kettle is evacuated to -0.08 MPa, deionized water and seed emulsion are added, stirred and heated to 55°C; initiator is added;

[0082] (2) adding dropwise a mixture solution of styrene, butadiene, carboxylic acid monomer, and molecular weight regulator to carry out free radical emulsion polymerization at a polymerization temperature of 55° C. for a dropwise addition time of 6 h, and heating to 70° C. for 3 h;

[0083] (3) After cooling, the pH value is adjusted to 6-7 with an alkaline substance, and after filtering, an adhesive is obtained.

[0084] Example 4

[0085] An adhesive, the raw material composition of which includes the following components in parts by weight, see Table 7;

[0086] Table 7

[0087] Specific compounds Quality (parts) Deionized water 119 Seed lotion 4 Styrene 60 Butadiene 40 Carboxylic acid monomer: methacrylic acid 1.2 Molecular weight regulator: n-dodecyl mercaptan 0.2 Molecular weight regulator: n-butyl mercaptan 1 Initiator: ammonium persulfate 1.2 Initiator: Ferrous sulfate 0.6 Alkaline substances: potassium hydroxide 0.6 Alkaline substances: sodium hydroxide 1

[0088] The seed emulsion includes the following components in parts by weight, see Table 8;

[0089] Table 8

[0090]

[0091]

[0092] A. A method for preparing a seed emulsion comprises the following steps:

[0093] S1. After the polymerization kettle is evacuated to -0.08MPa, deionized water and cationic emulsifier are added, stirred and heated to 65°C;

[0094] S2, add initiator, carboxymethyl cellulose, lignin, sodium bicarbonate, react for 3 hours, heat to 65°C and keep warm for 1 hour to obtain the product.

[0095] B. A method for preparing an adhesive, comprising the following steps:

[0096] (1) After the polymerization kettle is evacuated to -0.08 MPa, deionized water and seed emulsion are added, stirred and heated to 55°C; initiator is added;

[0097] (2) adding dropwise a mixture solution of styrene, butadiene, carboxylic acid monomer, and molecular weight regulator to carry out free radical emulsion polymerization at a polymerization temperature of 70° C. for a dropwise addition time of 5 h, and heating to 70° C. for 2 h;

[0098] (3) After cooling, the pH value is adjusted to 6-7 with an alkaline substance, and after filtering, an adhesive is obtained.

[0099] Example 5

[0100] An adhesive, the raw material composition of which includes the following components in parts by weight, see Table 9;

[0101] Table 9

[0102]

[0103]

[0104] The seed emulsion includes the following components in parts by weight, see Table 10;

[0105] Table 10

[0106] Specific compounds Quality (parts) Deionized water 183 Cationic emulsifier: Methyl dodecyl ammonium chloride 5 Initiator: ammonium persulfate 1.2 Initiator: Ferrous sulfate 0.6 Carboxymethyl cellulose 9 Lignin 35 Sodium bicarbonate 2

[0107] A. A method for preparing a seed emulsion comprises the following steps:

[0108] S1. After the polymerization kettle is evacuated to -0.08MPa, deionized water and cationic emulsifier are added, stirred and heated to 65°C;

[0109] S2, add initiator, carboxymethyl cellulose, lignin and sodium bicarbonate, react for 1 hour, raise the temperature to 65°C and keep it for 1.5 hours to obtain the product.

[0110] B. A method for preparing an adhesive, comprising the following steps:

[0111] (1) After the polymerization kettle is evacuated to -0.08 MPa, deionized water and seed emulsion are added, stirred and heated to 55°C; initiator is added;

[0112] (2) adding dropwise a mixture solution of styrene, butadiene, carboxylic acid monomer, and molecular weight regulator to carry out free radical emulsion polymerization at a polymerization temperature of 50° C. for a dropwise addition time of 5 h, and heating to 50° C. for 1 h;

[0113] (3) After cooling, the pH value is adjusted to 6-7 with an alkaline substance, and after filtering, an adhesive is obtained.

[0114] Comparative Example 1

[0115] The only difference from Example 1 is that in the preparation method of B, adhesive, the dropping time of step (2) is 3.5 h.

[0116] Comparative Example 2

[0117] The only difference from Example 1 is that, in A, the method for preparing the seed emulsion, the temperature of step S1 is 48° C.; and in B, the method for preparing the adhesive, the temperature of the free radical emulsion polymerization in step (2) is 48° C.

[0118] Comparative Example 3

[0119] The only difference from Example 1 is that the amount of the raw material cationic emulsifier: methyl dodecyl ammonium chloride is different, which is 9 parts.

[0120] Comparative Example 4

[0121] The only difference from Example 1 is that the raw material sodium bicarbonate is replaced by sodium carbonate.

[0122] Comparative Example 5

[0123] Commercially available product, special adhesive for ALC panels produced by Rizhao Guangda Chemical Co., Ltd.

[0124] Effect Example

[0125] The products prepared in Examples 1 to 5 and Comparative Examples 1 to 5 of the present application were tested for application performance, and the test standards or methods were as follows:

[0126] 1. The sound insulation test shall be carried out using the method specified in GB / T 30100-2013.

[0127] 2. The surface density test is carried out using the method specified in GB / T 30100-2013.

[0128] 3. Compressive strength test shall be carried out using the method specified in GB / T 19889.

[0129] The products prepared in Examples 1 to 5 of the present application and Comparative Examples 1 to 5 were subjected to application performance tests, and the test results are shown in Table 11.

[0130] Table 11

[0131] Test items Sound insulation(dB) <![CDATA[Areal density (kg / m 2 )]]> Compressive strength(MPa) Example 1 40 67 4.3 Example 2 38 74 4.8 Example 3 42 75 4.2 Example 4 48 68 4.1 Example 5 45 72 4.2 Comparative Example 1 31 83 3.6 Comparative Example 2 28 75 3.5 Comparative Example 3 33 82 3.8 Comparative Example 4 33 85 4.0 Comparative Example 5 40 81 4.2

[0132] The sound insulation volume ≥35dB, surface density ≤80kg / ㎡, and compressive strength ≥4MPa meet the requirements.

[0133] Since the technical solution of the present invention uses a special cationic emulsifier to form pores during the latex drying process, the pores of the formed board can be evenly distributed, and the sound insulation effect of the board is further improved while ensuring the surface density. At the same time, the special core-shell design can improve the compressive strength of the material. Therefore, it can be widely used in the following fields:

[0134] 1. Construction industry: Sound insulation is an important consideration in building design and construction. This technical solution can be applied to the manufacture of sound insulation walls, sound insulation doors and windows in buildings to improve indoor sound insulation and create a more comfortable living environment.

[0135] 2. Automobile industry: With the continuous development of the automobile market, consumers have higher and higher requirements for the quietness and comfort of automobiles. This technical solution can be applied to the manufacture of automobile interior materials to improve the sound insulation effect in the car and enhance the driving experience.

[0136] 3. Electronic products: Electronic products often generate noise during use, affecting the user experience. This technical solution can be applied to the manufacture of electronic product shell materials to reduce noise transmission and improve product quality.

[0137] 4. Industrial equipment: In some industrial equipment that requires noise control, such as fans, air-conditioning equipment, etc., this technical solution can be applied to the manufacture of sound insulation materials to reduce the impact of industrial equipment noise on the environment and human body and improve the quietness of the working environment.

[0138] Due to the increasing market demand in the above application areas, this technical solution has broad market prospects. As people's requirements for comfort and environmental quality continue to increase, the demand for sound insulation materials will also continue to increase, providing a good opportunity for the application and market promotion of this technical solution.

[0139] Although the present disclosure has been disclosed above through the description of the specific embodiments of the present disclosure, it should be understood that those skilled in the art can design various modifications, improvements or equivalents to the present disclosure within the spirit and scope of the attached scheme. These modifications, improvements or equivalents should also be considered to be included in the scope of protection claimed by the present disclosure.

Claims

1. A raw material composition for an adhesive, characterized in that: It contains the following raw materials in parts by weight: 3-6 parts of seed emulsion, 60 parts of styrene, 30-40 parts of butadiene, 1-3 parts of carboxylic acid monomer, 0.5-1.5 parts of molecular weight regulator, 0.8-2 parts of initiator, 0.5-2 parts of alkaline substance; Wherein, the seed emulsion comprises a cationic emulsifier and sodium bicarbonate.

2. The adhesive raw material composition according to claim 1, characterized in that: The carboxylic acid monomer is selected from acrylic acid and / or methacrylic acid; And / or, the molecular weight regulator is selected from one of n-dodecyl mercaptan, tert-dodecyl mercaptan and n-butyl mercaptan; And / or, the initiator is selected from one of ammonium persulfate / sodium bisulfite, potassium persulfate / sodium bisulfite, hydrogen peroxide / tartaric acid, hydrogen peroxide / diaobaikuai, ammonium persulfate / ferrous sulfate, hydrogen peroxide / ferrous sulfate, wherein the ratio of oxidant:reducing agent is 1:0.2-0.8; And / or, the alkaline substance is selected from alkali metal hydroxides, preferably, the alkaline substance is sodium hydroxide or potassium hydroxide; And / or, the raw material composition of the adhesive further comprises deionized water; preferably, the weight proportion of the deionized water is 100 to 120 parts.

3. The raw material composition of the adhesive according to claim 1, characterized in that: The seed emulsion comprises the following raw materials in parts by weight: 183-210 parts of deionized water, 3-8 parts of cationic emulsifier, 1-2 parts of initiator, 5-10 parts of carboxymethyl cellulose, 35 parts of lignin, and 1-3 parts of sodium bicarbonate.

4. The adhesive raw material composition according to claim 3, characterized in that: The cationic emulsifier is selected from at least one of methyl alkyl ammonium chloride; And / or, the molecular weight of the lignin is 500-1000.

5. A method for preparing an adhesive, characterized in that: The raw material of the ALC sheet adhesive comprises the raw material composition of the adhesive as described in any one of claims 1 to 4, and specifically comprises the following steps: (1) After the polymerization kettle is evacuated, deionized water and seed emulsion are added, stirred and heated to 50-60°C, and an initiator is added; (2) adding a mixed solution of styrene, butadiene, carboxylic acid monomer and molecular weight regulator dropwise for free radical emulsion polymerization for 4 to 6 hours, and then carrying out heat preservation reaction; (3) After cooling, the pH value is adjusted with an alkaline substance, and the mixture is filtered to obtain the ALC sheet adhesive.

6. The method for preparing the adhesive according to claim 5, characterized in that: The preparation method satisfies at least one of the following conditions: In step (1), the vacuum degree of the polymerization kettle is -0.08 MPa; In step (2), the temperature of the free radical emulsion polymerization is 50-60° C.; In step (2), the temperature of the insulation reaction is 50 to 70° C.; In step (2), the insulation reaction time is 1 to 3 hours; In step (3), the pH value is adjusted to 6-7.

7. The method for preparing the adhesive according to claim 5, characterized in that: In step (1), the method for preparing the seed emulsion comprises the following steps: S1. After the polymerization kettle is evacuated, deionized water and cationic emulsifier are added, stirred, and the temperature is raised to 60-70°C; S2, adding an initiator, carboxymethyl cellulose, lignin and sodium bicarbonate to react, and keeping the temperature after the reaction is completed to obtain the seed emulsion.

8. The method for preparing the adhesive according to claim 7, characterized in that: The preparation method satisfies at least one of the following conditions: In step S1, the vacuum degree of the polymerization kettle is -0.08MPa; In step S2, the reaction time is 1 to 3 hours; In step S2, the insulation reaction time is 1 to 2 hours; In step S2, the temperature of the heat preservation reaction is 60-70°C.

9. An adhesive, characterized in that: The adhesive is prepared by the method for preparing the adhesive according to any one of claims 5 to 8.

10. Use of the adhesive according to claim 9 in ALC boards.